HD+ photodissociation in the scaled coordinate approach - Roudnev, Vladimir; Esry, B. D. (My University, 2005)
The scaled coordinate approach is applied to the problem of HD+ photodissociation in a short, intense, infrared laser pulse. Two- and three-dimensional models for the molecule aligned in the field of a linearly polarized laser are studied. Scaling allows substantial improvements in the numerical accuracy and provides a simple way to calculate the fragments’ energy spectra.